ENGLISH BORROWINGS IN MODERN FRENCH AND UKRAINIAN LANGUAGES - Ruban, Vira (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The evolution of the language while some obsolete elements disappear and new elements appear is the fundamental condition for the existence of any national language which is the main means of communication of the people. In its evolution, the language is enriched by various means, and the linguistic contacts play an important role in the enrichment of languages. Today when the process of globalization is becoming a defining feature of the development of humanity, the issues of interaction and mutual influence of languages have acquired a particular relevance. The end of the 20th and the beginning of the 21st century are characterized by the intensive diffusion in the world of English which, due to the economic, technical, military and political power of the United States, has become the language of international communication and so, the main source of borrowings for languages throughout the world. The article considers the influence of English on the development of modern French and Ukrainian languages, presents a comparative analysis of the process of borrowing and adaptation of English elements in the receiving language, analyzes the reasons why this process is different in Romance and Slavic languages. The study shows that these are the extralinguistic factors that have become decisive in the process of lexical borrowings at the current stage of language development. We can see that European languages, are going through a particular period in their history, accepting a large number of lexemes from English. That is why linguists from different countries have started to focus on the question of preserving this precious and important heritage for each national culture. There are attempts to use internal means of the language to enrich it, but the created lexemes are still not as attractive to speakers due to the external factors that come into play and promote the penetration and integration of Anglicisms into European languages.____________References:• Etiemble, R. (1964). Parlez-vous franglais.• Léopold, J. (2021) Sommes-nous [réellement] envahis par les anglicismes ? Deux décennies d’anglicismes, Lengas, 89. DOI : https://doi.org/10.4000/lengas.5200• Pergnier, (1989). Les anglicismes. PUF.• Saugera, V. (2017). La fabrique des anglicismes. Travaux de linguistique, 75(2), 59– DOI: 10.3917/tl.075.0059• Zanola, T. (2008) Les anglicismes et le français du XXI siècle: La fin du franglais? Synergies Italie, № 4, 87–96.
Keywords: English borrowings, anglicism, adaptation of borrowings, frenglish, excessive borrowings, language contacts, source language